Psychological readiness for marriage of boys and girls during their student years - Elena A. Mannanova; Alexandra A. Nikitinа (Russian Journal of Education and Psychology, 2025)
Background. Modern society is undergoing a transformation of marital and family values, which is manifested in an increasing number of divorces, postponement of marriage to a later age and the spread of alternative forms of relationships (cohabitation, childfree). The student period is key for the formation of marital and family attitudes, however, research shows that only 5% of students demonstrate sufficient readiness for family life. Despite the relevance of the topic, there are not enough works studying the specifics of psychological readiness for marriage among students. This determines the need for research to identify the level and characteristics of such readiness, taking into account gender differences.